The Influence of Quality of Pharmaceutical Installation Services on Outpatient Satisfaction at Malahayati Islamic Hospital Medan in 2023 - Dessy Mariana; Arifah Devi Fitriani; Endang Maryanti (Universitas Ibn Khaldun Bogor, 2024)
This study highlights outpatient satisfaction with pharmaceutical services at the Malahayati Islamic Hospital in Medan in 2023. Data shows a decrease in outpatient visits of 21.5% in July 2023 at this hospital. The waiting time for taking medication exceeds 60 minutes, and can even reach two to three days, indicating that there is concern about the effectiveness of pharmaceutical services in the Pharmacy Installation. The research aims to analyze the impact of the quality of pharmaceutical installation services on outpatient satisfaction by involving 100 outpatients in quantitative research using a cross-sectional approach in August-September 2023. The results of the analysis show that service quality significantly influences outpatient satisfaction, especially in the dimensions of effective, efficient, timely, patient-focused, fair, safe, and integrated. The most dominant factors are fairness and safety, which significantly influence patient satisfaction. This study recommends improvements in the form of adding pharmacists, better medication planning, providing WiFi services, routine communication training for staff, and completing identity information and telephone numbers in patient medical records. In conclusion, the quality dimensions of pharmaceutical services greatly influence outpatient patient satisfaction, and improvements in fair and safe aspects can increase patient satisfaction.